Penentuan Lintasan Pergerakan Quadcopter Berbasis GPS (Global Positioning System) - Abdur Rohman Harits Martawireja; Hadi Supriyanto (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2019)
UNMANNED AERIAL VEHICLE (UAV) is an aerial vehicle without pilot that can be controlled. There are two types of UAV, fixed wing and rotary wing. Quadcopter becomes one of rotary wing type UAV that is commonly used in various needs, like exploration and imaging. In this study, Quadcopter is used as the vehicle that moves following the path produced by the GPS on followed objek (main modul). The type of the GPS installed on Quadcopter (GPS1) and main modul (GPS2) are GPS Ublox NEO. The working principle of the system is Quadcopter follows the track coordinates generated by GPS1, which GPS1 track data is sent to the Quadcopter using Bluetooth media. While the Quadcopter moves, it will continuously compare the coordinate data produced by the Quadcopter's position with the track coordinate data that had been received. Testing on the Main Module GPS Receiver (GPS1) and GPS Receiver Quadcoter (GPS2), both GPS is able to get GPS data from satellites, but data can be lost or deviated in confined spaces. Error / difference in data from GPS1 and GPS2 in Quadcopter movement testing to follow the Main Module as the destination point at latitude and longitude, respectively, are 53% and 51%.